PENGEMBANGAN LEMBAR KERJA SISWA DENGAN BANTUAN DIGITAL MIND MAPS UNTUK MELATIH KETERAMPILAN BERPIKIR KREATIF SISWA SMAN 8 KOTA BENGKULU - Maningsih, Sulianti Angrum; Fitriani, Apriza (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to determine the validity of worksheets with the help of digital mind maps to improve creative thinking skills in excretory system materials and know the response of teachers and students to LKS with the help of digital mind maps to practice creative thinking skills in the excretory system material. LKS development uses the ADDIE development model which is modified into 4 stages (Analysis, Design, Development, Implementation). The data collection technique in this study was carried out by distributing validation questionnaires which were used to test the validity of the developed product, while the response questionnaire was used to determine the responses of teachers and students to the developed product. The results of this study indicate that: 1) the results of validation by material experts and media experts on student worksheets with the help of digital mind maps get an average score of 3.51 with a very valid category. 2) Biology subject teachers' responses to student worksheets get an average score of 3.86 with a very practical category. Meanwhile, student responses to student worksheets get an average score of 3.24 in the practical category. Kata kunci: digital mind maps, keterampilan berpikir kreatif, LKS, sistem ekskresi